2018
DOI: 10.1002/smll.201801897
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Codoped Unique Carbon with 0.4 nm Ultra‐Micropores for Ultrahigh Areal Capacitance Supercapacitors

Abstract: A full understanding of ion transport in porous carbon electrodes is essential for achieving effective energy storage in their applications as electrochemical supercapacitors. It is generally accepted that pores in the size range below 0.5 nm are inaccessible to electrolyte ions and lower the capacitance of carbon materials. Here, nitrogen-doped carbon with ultra-micropores smaller than 0.4 nm with a narrow size distribution, which represents the first example of electrode materials made entirely from ultra-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…The key to success of HCSs in various applications is based on the availability of precisely controlled diameter and shell thickness, surface chemistry, and dispersibility in media. Numerous investigations have been devoted to the synthesis of porous carbon spheres via various strategies, including hard or soft‐templating method, emulsion self‐assembly process, and stöber‐based routes . Among the studies reported, many have focused on the preparation of hollow structural units with tunable sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The key to success of HCSs in various applications is based on the availability of precisely controlled diameter and shell thickness, surface chemistry, and dispersibility in media. Numerous investigations have been devoted to the synthesis of porous carbon spheres via various strategies, including hard or soft‐templating method, emulsion self‐assembly process, and stöber‐based routes . Among the studies reported, many have focused on the preparation of hollow structural units with tunable sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller semicircle of HPC-1 than those of the other samples at highfrequency region of the EIS spectra indicates its much better electrochemical capacitive properties, lower charge transfer resistance and diffusion resistance. [57] The slope at low fre-quency becomes much steeper for HPC-1, confirming its higher capacitive behavior. The relationship between the specific capacitance and the loading current density of the samples are plotted in Figure 6e.…”
Section: Resultsmentioning
confidence: 77%
“…hold that the semicircle loop was ascribed to the resistance between active material particles and the contact resistance at the current collector/active material. The smaller semicircle of HPC‐1 than those of the other samples at high‐frequency region of the EIS spectra indicates its much better electrochemical capacitive properties, lower charge transfer resistance and diffusion resistance . The slope at low frequency becomes much steeper for HPC‐1, confirming its higher capacitive behavior.…”
Section: Resultsmentioning
confidence: 92%
“…[ 35 ] Mass change recorded by EQCM revealed that the nanopores in N‐doped carbon microspheres (pore size < 0.4 nm) are accessible for both cations and anions, harnessing high capacitance of 330 µF cm −2 (normalized to surface area). [ 36 ] However, linear gravimetric quantification is only conclusive when no dissipation factor (the ratio of full resonance width peak to the related resonance frequency) variation is involved. [ 14 ] In this case, hydrodynamic spectroscopy (EQCM‐D) needs to be incorporated, which can operate under different overtones enabling different penetration depth.…”
Section: Mechanism Understanding Of Electrochemical Supercapacitorsmentioning
confidence: 99%